Trade control measures in Caricom Member States (CEDP St. MichaelBB, 1992)
Includes in the overall report, a series of country files which contain various pieces of legislation, regulations and administrative orders relating to trade control measures.
At head of title: Caricom Export Development Project (CEDP)